The T‐cell fingerprint of MALT1 paracaspase revealed by selective inhibition. Issue 1 (21st December 2017) - Bardet, Maureen; Unterreiner, Adeline; Malinverni, Claire; Lafossas, Frédérique; Vedrine, Corinne; Boesch, Danielle; Kolb, Yeter; Kaiser, Daniel; Glück, Anton; Schneider, Martin A; Katopodis, Andreas; Renatus, Martin; et al.
Abstract: Mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1) is essential for immune responses triggered by antigen receptors but the contribution of its paracaspase activity is not fully understood. Here, we studied how MALT1 proteolytic function regulates T‐cell activation and fate after engagement of the T‐cell receptor pathway. We show that MLT‐827, a potent and selective MALT1 paracaspase inhibitor, does not prevent the initial phase of T‐cell activation, in contrast to the pan‐protein kinase C inhibitor AEB071. However, MLT‐827 strongly impacted cell expansion after activation. We demonstrate this is the consequence of profound inhibition of IL‐2 production as well as reduced expression of the IL‐2 receptor alpha subunit (CD25), resulting from defective canonical NF‐κB activation and accelerated mRNA turnover mechanisms. Accordingly, MLT‐827 revealed a unique transcriptional fingerprint of MALT1 protease activity, providing evidence for broad control of T‐cell signaling pathways. Altogether, this first report with a potent and selective inhibitor elucidates how MALT1 paracaspase activity integrates several T‐cell activation pathways and indirectly controls gamma‐chain receptor dependent survival, to impact on T‐cell expansion. Abstract : MLT‐827 is the first potent and selective Mucosa‐associated lymphoid tissue lymphoma translocation protein 1 (MALT1) paracaspase inhibitor. It does not block the initial phase of T‐cell activation. However, work with MLT‐827 elucidates how MALT1 paracaspase activity integrates several T‐cell activation pathways and indirectly controls gamma‐chain receptor dependent survival, to impact on T‐cell expansion.